PARTISIPASI MASYARAKAT LOKAL DALAM PENGELOLAAN USAHA WISATA DI KOTA SENTANI, KABUPATEN JAYAPURA, PAPUA - Nani Eunike Manoach; IGPB. Sasrawan Mananda; I Nyoman Sudiarta (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
Local community participation in managing of local industry is important to tourism development in Sentani City, Jayapura Regency, Papua. The purpose of this study is to determine the participation of local community in the tourism industry entrepreneurship in Sentani City. The informant determination technique used in this research was purposive technique and the data analyze technique used in research was qualitative descriptive. The study result showed that local people in Sentani, have impulsive participation in tourist attraction business, waterpark, rent boats, and handycraft business. Coersive participation in rent car business, tour and travel, restaurant, and accommodation business. Induced participation in tour guide business.